2021
DOI: 10.1097/aog.0000000000004367
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Antibodies in Neonatal Cord Blood After Vaccination in Pregnancy

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 12 publications
1
44
0
2
Order By: Relevance
“…Interestingly, our case also confirms the presence of neutralizing antibodies in the umbilical cord blood ( Table 1 ). Another case demonstrated that the antibody subtypes, which are transferred, possess a neutralizing capacity, although a clear description of the neutralization assay that was used was not provided [ 41 ]. It is also interesting to note that total antibodies and NAbs titers in the maternal blood were at the lower range in our control cohort ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our case also confirms the presence of neutralizing antibodies in the umbilical cord blood ( Table 1 ). Another case demonstrated that the antibody subtypes, which are transferred, possess a neutralizing capacity, although a clear description of the neutralization assay that was used was not provided [ 41 ]. It is also interesting to note that total antibodies and NAbs titers in the maternal blood were at the lower range in our control cohort ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of these adverse effects is also likely to be reduced by vaccination, therefore, women should be counseled about the probable additional benefits of vaccination over and above protection from severe disease (Table 2). The presence of anti‐SARS‐CoV‐2 IgG was reported in the neonate of a vaccinated mother 24 , however, it is not yet possible to say what impact maternal vaccination will have on neonatal protection against infection after birth.…”
Section: Risk Factors For Developing Severe Covid‐19 Risk Factors For Contracting Covid‐19mentioning
confidence: 99%
“…Furthermore, vaccination is likely to protect not only the pregnant woman but also the fetus/neonate. With regards to SARS-CoV-2 vaccines, a recent case report demonstrated transplacental transmission of antibodies against the spike protein following vaccination of the mother 24 .…”
Section: Available Sars-cov-2 Vaccines and Their Safety Profilesmentioning
confidence: 99%
“…A preliminary finding of mRNA safety of COVID-19 vaccine in pregnant women showed that vaccination is safe in the third trimester of pregnancy ( Shimabukuro et al., 2021 ). In addition to vaccination protecting women against COVID-19 and its complications during pregnancy, emerging evidence has shown transplacental transfer of SARS-CoV-2 antibodies after maternal COVID-19 vaccination during the third trimester, which suggests that maternal vaccination might provide some level of protection to the neonate ( Gill and Jones, 2021 ; Gray et al., 2021 ; Rottenstreich et al., 2021 ). To date, there is still little information on the efficacy and safety of vaccinating pregnant women.…”
Section: Preventionmentioning
confidence: 99%